solve the intergrating factt ;tdt+xdx=a2(tdx-xdx)/t^2+x^2
Solve the integrating factor:
"tdt+xdx=\\frac{a^2(tdx-xdt)}{t^2+x^2}"
Solution:
"(x-\\frac{a^2t}{t^2+x^2})dx+(t+\\frac{a^2x}{t^2+x^2})dt=0"
"Pdx+Qdt=0"
where "P=(x-\\frac{a^2t}{t^2+x^2})" and "Q=(t+\\frac{a^2x}{t^2+x^2})" .
Let's find "\\frac{\\partial P}{\\partial t}" and "\\frac{\\partial Q}{\\partial x}":
"\\frac{\\partial P}{\\partial t}=-a^2\\cdot\\frac{x^2+t^2-2t^2}{(t^2+x^2)^2}=a^2\\cdot\\frac{t^2-x^2}{(t^2+x^2)^2}";
"\\frac{\\partial Q}{\\partial x}=a^2\\cdot\\frac{t^2+x^2-2x^2}{(t^2+x^2)^2}=a^2\\cdot\\frac{t^2-x^2}{(t^2+x^2)^2}" .
Since "\\frac{\\partial P}{\\partial t}=\\frac{\\partial Q}{\\partial x}" than we can conclude that it is a total differential equation.
Its solution can be find as:
"U(x,t)=\\int_{x_0}^x P(\\tau,t_0)d\\tau+\\int_{t_0}^t Q(x,\\tau)d\\tau"
where "x_0" and "t_0" are any values that can be freely chosen. Let's choose "x_0=1", "t_0=0" .
"U(x,t)=\\int_{1}^x (\\tau-\\frac{a^2\\cdot0}{0^2+\\tau^2})d\\tau+\\int_{0}^t (\\tau+\\frac{a^2x}{\\tau^2+x^2})d\\tau="
"\\int_{1}^x \\tau d\\tau+\\int_{0}^t (\\tau+\\frac{a^2x}{\\tau^2+x^2})d\\tau=" "\\frac{x^2}{2}-\\frac12+\\frac{t^2}{2}+a^2\\arctan{\\frac {t}{x}}" .
So the general integral of the equation has the form:
"\\frac{x^2}{2}+\\frac{t^2}{2}+a^2\\arctan{\\frac {t}{x}}=const" .
Answer:
This equation is a total differential equation therefore, its solution can be found without an integrating factor or any constant value can be used as integrating factor in this case.
Solution: "\\frac{x^2}{2}+\\frac{t^2}{2}+a^2\\arctan{\\frac {t}{x}}=const" .
Comments
Leave a comment